Teacher Talk In English Teaching And Learning Process At SMA N 2 Klaten In 2015/2016 Academic Year - Dyah Ayu Malikha, Denissa, Prof. Endang Fauziati, M.Hum (2016)
This study is conducted to find out the language used and the types of Teacher Talk in teaching and learning process at SMA N 2 Klaten. The aims of this study are: (1) to describe the languages of teacher talk used in English teaching and learning process, (2) the dominant language of Teacher Talk, (3) the types of Teacher Talk (4) the dominant type of Teacher Talk in English teaching and learning process at SMA N 2 Klaten 2015/2016 academic years. This research was conducted through descriptive qualitative method, especially naturalistic study in analyzing the data. An Foreign Language Interaction Analysis (FLINT) from Moskowitzt was used to analyze the data. In order to gather the data, this study used two methods of collecting, they were: observation, recording and interview. The result of the study showed that there are five language used in Teacher Talk during English teaching and learning process at SMA N 2 Klaten. The kind of language used in Techer Talk are: English, Indonesia language, Javanese, Arabic language, and Mix language. English was the dominant language during teaching and learning process at SMA N 2 Klaten. The teacher tried to use English as much as possible. There are some types of teacher talk are used by the teachers, such as deals with feelings, praises or encourages, jokes, uses ideas of students, repeats student response verbatim, asks questions, gives information, corrects without rejection, gives direction, criticizes student behaviour, criticizes student response, and greetings. Asks question and gives information are the dominant types in teacher's way of conducting teaching and learning activities. It proven by the percentage of these types that takes up 39% times to asks question and 22% times to gives information. The conclusion of this research is that the English teacher at SMA N 2 Klaten used various language and types on teacher talk. The teacher used types 4 (asks question) to increase interaction during teaching and learning process. The teacher used English as much as possible in order to improve the students' ability. Various language and type of teacher talk can make the student interested in English teaching-learning process.